Japan's comfort women : sexual slavery and prostitution during World War II and the US occupation - Tanaka, Toshiyuki, 1949- (Asia's transformations., 2003)
Japan's Comfort Women tells the harrowing story of the ""comfort women"" who were forced to enter prostitution to serve the Japanese Imperial army, often living in appalling conditions of sexual slavery. Using a wide range of primary sources, the author for the first time links military controlled prostitution with enforced prostitution. He uncovers new and controversial information about the role of the US' occupation forces in military controlled prostitution, as well as the subsequent ""cover-up"" of the existence of such a policy. This groundbreaking book asks why US occupation